PENGGUNAAN PESTISIDA RACUN POLYDOR UNTUK MENGENDALIKAN HAMA KUMBANG TANDUK PADA AREAL KELAPA SAWIT BELUM MENGHASILKAN DI PERKEBUNAN AEK NABARA PT. SUPRA MATRA ABADI LABUHAN BATU, SUMATERA UTARA - Ronal Triadi; Khairul Rizal; Novilda Elizabeth Mustamu; Fitra Syawal Harahap (Agros Journal of Agriculture Science, 2023)
Oil palm (Elaeis guineensis Jacq) is a plantation crop that has an important role in advancing the economy and agriculture in Indonesia. This can be proven by the increase in the standard of living of farmers who experience an increase in area and production every year. The challenge of increasing the area of oil palm plantations apart from the limited available land is also the attack of plant-disturbing organisms (OPT), particularly pests. The increasing use of large-scale land for oil palm cultivation in Indonesia has increased the amount of monoculture land that is favorable for pest development. Field Work Practice Activities (PKL) carried out at PT. Supra Matra Abadi (SMA) Aek Nabara, Bilah Hulu District, Labuhanbatu Regency, Postal Code (21462) This activity was carried out for four months, starting from 21 February - 21 July 2022. Conducting survey research on horn beetle populations and treatment areas Before conducting research, it is necessary to find a place to area of young plants, immature plants which are often attacked by horn beetles either in one block or several blocks. After that, a place was determined for each level of treatment. This study used a completely randomized design (CRD) method with 3 treatment levels, including: 1. Control/without polydor pesticide treatment 2. Spraying polydor pesticide with a dose of 150 cc/pkk 3. Spraying polydor pesticide dose 160 cc/pkk research using 3 In repetition at each level of treatment, spraying polydor pesticide using a concentration of 1% on the outside and inside. Observations were analyzed with variance at the 5% significance level. To find out the differences between treatments, the DMRT test was used with a significant level of 5%. Based on research results at PT. It can be concluded that the insecticide treatment polydor 150cc/pkk and 160cc/pkk on afd IV was very effective in controlling horn beetle attacks.Kelapa sawit (Elaeis guineensis Jacq) merupakan tanaman perkebunan yang memiliki peran penting dalam memajukan perekonomian dan pertanian di Indonesia. Hal ini dapat dibuktikan dengan meningkatnya taraf hidup petani yang mengalami peningkatan luas dan produksi setiap tahunnya. Tantangan peningkatan luas perkebunan kelapa sawit selain keterbatasan lahan yang tersedia juga merupakan serangan organisme pengganggu tumbuhan (OPT), khususnya hama. Meningkatnya penggunaan lahan skala besar untuk budidaya kelapa sawit di Indonesia telah meningkatkan jumlah lahan monokultur yang menguntungkan bagi perkembangan hama. Kegiatan Praktek Kerja Lapang (PKL) yang dilaksanakan di PT. Supra Matra Abadi (SMA) Aek Nabara Kecamatan Bilah Hulu Kabupaten Labuhanbatu Kode Pos (21462) Kegiatan ini dilaksanakan selama empat bulan yaitu mulai tanggal 21 Februari – 21 Juli 2022. Melakukan penelitian survey populasi kumbang tanduk dan daerah perlakuan Sebelum melakukan penelitian, perlu dicari tempat untuk tanaman muda, tanaman belum menghasilkan yang sering diserang kumbang tanduk baik dalam satu blok maupun beberapa blok. Setelah itu, ditentukan tempat untuk setiap tingkat perlakuan. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) dengan 3 taraf perlakuan, antara lain: 1. Kontrol/tanpa perlakuan pestisida polydor 2. Penyemprotan pestisida polydor dengan dosis 150 cc/pkk 3. Penyemprotan pestisida polydor dosis 160 cc/pkk menggunakan 3 Di ulangi pada setiap tingkat perlakuan, penyemprotan pestisida polydor menggunakan konsentrasi 1% di bagian luar dan dalam. Pengamatan dianalisis dengan varians pada tingkat signifikansi 5%. Untuk mengetahui perbedaan antar perlakuan digunakan uji DMRT dengan taraf nyata 5%. Berdasarkan hasil penelitian di PT. Dapat disimpulkan bahwa perlakuan insektisida polydor 150cc/pkk dan 160cc/pkk pada afd IV sangat efektif dalam mengendalikan serangan kumbang tanduk.